Potential of NT-proBNP and sST2 rapid tests in patients with acute myocardial infarction - V. V. Ryabov; E. V. Kruchinkina; E. V. Vyshlov; A. M. Gusakova; A. V. Darya; O. O. Panteleev; Na. Y. Margolis; T. E. Suslova (Российский кардиологический журнал)
Aim. To compare two methods for the determination of N-terminal pro-brain natriuretic peptide (NT-proBNP) and soluble ST2 (sST2): rapid immunochemical methods and standard enzyme immunoassay (ELISA), as well as to determine the possibility of rapid tests for determining these biomarkers in acute myocardial infarction (AMI).Material and methods. This open, non-randomized, single-center observational study included 41 patients: 20 with non-ST-elevation myocardial infarction (non-STEMI) and 21 with ST-elevation myocardial infarction (STEMI), without cardiogenic shock and active inflammatory process. During hospitalization, all patients underwent the level of NT-proBNP using an immunological fluorometric analyzer AQT90 FLEX (Radiometer, Germany) and sST2 immunological method for assessing lateral flow using an ASPECT Reader™ T2 analyzer (Critical diagnostics, USA). Then, studies of these biomarkers by standard ELISA were delayed.Results. The Spearman correlation coefficient for rapid NT-proBNP and NT-proBNP-ELISA was 0,5937 (p=0,00000087). At the same time, the proportion of patients with an NT-proBNP level >300 pg/ml in the rapid test was significantly higher than in the ELISA: 90% vs 44% (p<0,05). In a comparative analysis of two methods for sST2, the Spearman correlation coefficient for rapid sST2 and sST2-ELISA is 0,9561 (p=0,0000007). The proportions of patients with sST2 >35 ng/ml with rapid and ELISA methods did not differ significantly and amounted to 53 and 55%. Rapid NT-proBNP were significantly different between Killip I and Killip III (p=0,043): Me=1375,00 (669,00; 3140,00) vs Me=3660,00 (1815,00; 6890,00). There were no significant changes in the rapid sST2 level depending on Killip class.Conclusion. Correlations were found between rapid and ELISA methods in patients with AMI: medium in strength for NT-proBNP and strong for sST2. The proportion of patients with NT-proBNP levels >300 pg/mL in the rapid test was significantly higher than in the ELISA. Therefore, a conversion formula is needed, for which the available data are insufficient. The proportion of patients with sST2 >35 ng/ml in the rapid and ELISA methods did not differ significantly. A direct relationship between the level of rapid NT-proBNP and Killip class was found. No dependence of the level of rapid sST2 on Killip class was found.